REGULATING THE PROTECTION OF CRYPTOCURRENCY EXCHANGES TO PREVENT SYSTEMIC RISKS AND CONSUMER RIGHTS VIOLATIONS IN INDONESIA - Budi Hermono; Ellectrananda Anugerah Ash-sidiqqi; Rindia Fanny Kusumaningtyas; Mutiara Dwi Sari (Faculty of Law, Universitas Lampung, 2026)
The rapid growth of cryptocurrency trading in Indonesia presents both opportunities and systemic risks to the national financial system. Cryptocurrency exchanges, as digital asset intermediaries, remain vulnerable to fraud , cyberattacks, market manipulation, and regulatory uncertainty. This study examines the legal framework for exchange protection, highlighting the absence of integrated regulation combining financial security, consumer protection, and technological governance, despite the transfer of authority from Badan Pengawas Perdagangan Berjangka Komoditi or Bappepti to Otoritas Jasa Keuangan (OJK) or Financial Services Authority. Using a normative juridical approach and comparative analysis of Japan and Singapore, the findings show the need for an adaptive and integrated regulatory model that strengthens transparency, accountability, and consumer trust while supporting financial innovation. Establishing such a framework is essential to mitigate systemic risk, reinforce public trust and ensure sustainable financial development aligned with global governance standards and the Sustainable Development Goals (SDGs).